State-Of-Health Prediction Integrated With State-Of-Charge Monitoring Of A Lithium-Ion Battery Cell For Lifetime Prediction - Leow, Yoong Yang (Universiti Sains Malaysia, 2018)
In this FYP, a lithium-ion battery cell was monitored during its charge-and-discharge cycles in order to predict its State-of-Health (SoH) and estimate its State-of-Charge (SoC) for battery lifetime analysis. Lithium-ion battery will experience serious damage if exposed to overcharging and deep discharging for a long time, hence SoC estimation is crucial to help the user monitor the SoC of the battery, so the battery lifetime will not decrease due to overcharging or deep discharging. Besides, SoH prediction is used to indicate the health condition of the battery whether the battery still can operate or not since lithium-ion battery undergoes degradation as time passes. Battery lifetime analysis is performed to predict the remaining useful life of the battery, so the user can know the amount of charge-and-discharge cycles left before failure and then can prepare for the replacement in time, thus improving the system reliability. In this FYP, a simple battery management system (BMS) was developed. Then, SoC estimation was performed via Coulomb counting and OCV methods. SoH prediction was through the measurement of battery capacity. Lastly, the data obtained from SoH prediction was employed to predict the battery remaining useful life.